تطوير المعجم المساعد على كتاب تعليم اللغة العربية للصف الرابع بمستوى المدرسة الابتدائية - Nur Fajar Akbarwati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
إن تعليم اللغة العربية لا سيما في مدرسة أحمد ياني الإبتدائية الإسلامية المتكاملة مالانق لم تكن جودته خيرا. بناء على نتيجة الملاحظة والمقابلة مع المدرس، عرف أن تعليم اللغة العربية لا يجلب رغبة الطلاب بالنسبة إلى تعليم اللغة الأجنبية الأخرى مثل تعليم اللغة الإنجليزية لأن وسائل التعليم محدودة حتى يشعر الطلاب الصعب في بحث معنى المفردات فيحتاجوا إلى المعجم المساعد لتسهيل الطلبة والمعلم في التعليم اللغة العربية. منهج هذا البحث هو منهج البحث والتطوير (RD) نمط بورغ وغال. أما نتيجة التصديق من خبير المواد والمحتويات فهي 87 % ونتيجة التصديق من خبير التصميم هي 100%. هذه النتيجة تدل على أن المعجم المساعد الذي طورتها الكاتبة لائق جدا في تعليم اللغة العربية. وبناء على نتيجة الاختبار التائي (Ttest) بالاختبار التائي المجموعة الواحدة (Paired Sample T test) عرف أن قيمة T المحسوبة هي 13،346 وقيمة T بالجدوال هي 2،064. وهذا دليل على أن قيمة T المحسوبة أكبر من قيمة T بالجدوال. لذلك، استخلصت الكاتبة أن تعليم اللغة العربية باستخدام المعجم المساعد فعال.Learning Arabic especially in SDIT Ahmad Yani Malang have not good quality. Based on the observations and interviews with teachers it is known that the students are less fond of Arabic subjects compared with foreign language subjects namely English. Another case is the use of Arabic language learning media especially in the fourth class is still limited so that students feeling it very difficult to know and search the meaning of vocabulary of Arabic material. Therefore needed a supporting dictionary to facilitate teachers and students in the process of learning Arabic as a solution of the problem. This research research and development (R D) based on model from Borg and Gall. The result of validation the content and material experts is 87 % and the design expert's validation is 100 %. Based on the validation result from both experts, it can be concluded that this supporting dictionary is very suitable for use in the learning Arabic language. Based on the results of Ttest with Paired Sample TTest known THit value is 13.346 and TTabl value is 2, 064. This shows that the value of THit is greater than the value of TTabl it can be concluded that learning Arabic language are effective by using the dictionary support textbook